Developing an international social work education collaboration: A partnership approach between Monash University, Australia and University of Papua New Guinea. (November 2014) - Brydon, Kerry; Kamasua, John; Flynn, Catherine; Mason, Robyn; Au, Rosa; Ayius, Dora; Hampson, Ralph
In late 2009 staff from the Department of Social Work at Monash University in Australia responded to a call for expression of interest in becoming volunteers in a program sponsored by the Australian Group of Eight Universities that sought to strengthen teaching and curriculum development activities with the University of Papua New Guinea. The presenting request was for volunteers to conduct short teaching stints in Papua New Guinea. The discussion that follows considers some of the issues, challenges and opportunities involved in forging this international collaboration in social work education.